Thermal Reduction Method of DC-link Capacitors and SiC MOSFETs in Two-Level Inverters Based on Discontinuous PWM - Choi, Hye Won; Lee, Kyo Beum (2024 IEEE Energy Conversion Congress and Exposition, ECCE 2024 - Proceedings, 2024)
This paper proposes a thermal reduction method of DC-link capacitors and SiC MOSFETs in two-level inverters based on discontinuous PWM. The converter reliability has been extensively studied at both the device and the inverter levels through physics of failure analysis. The failures of switch modules and capacitors constitute about 50% of inverter system failures, primarily due to cumulative thermo-mechanical damage from power loss and thermal stress. The power loss and thermal behavior of switching modules are analyzed to reduce the rate of failures in this paper. The proposed method alleviates the thermal stress by applying discontinuous PWM, thereby decreasing power loss. Moreover, a phase-shifted scheme is applied to decrease the ripple current by reducing the loss and temperature of the DC-link capacitor, despite a deterioration in the total harmonic distortion (THD) of the output current. The proposed thermal reduction method is verified by simulation results.
Keywords: Dc-link; DC-link capacitor; Discontinuous PWM; Inverter-based; Powerloss; Reduction method; SiC module; SiC MOSFETs; Thermal reduction; Two-level inverters; DC-link capacitor; Discontinuous PWM; Reliability; SiC module; Thermal reduction